Soil property and crop yield responses to variation in land use and topographic position: Case study from southern highland of Ethiopia - Getahun Haile; China Gebru; Mulugeta Lemenih; Getachew Agegnehu (Elsevier, 2024)
Understanding soil property and crop yield responses to variations in land use and topographic gradient is vital for designing targeted soil and agronomic management practices. This study investigated the interrelationships between land use, topographic position, soil properties, and crop yield. Three replicates of three land use types - enset agroforestry, cropland (annual crop), and grazing land - were selected along a toposequence (upper, middle and lower) for the study. A total of 54 composite soil samples were collected and analyzed. Grain yield and above ground biomass were also gathered from the cropland and analyzed. Soil profile descriptions revealed notable variations in soil physical properties, including soil texture, bulk density, color, horizons, and depth among the pedons of the three topographic positions. Clay and silt fractions exhibited significant differences between land uses and topographic positions, while the sand fraction was influenced by topographic position alone. Crop and grazing lands displayed higher clay content compared to the enset field. A decreasing trend in clay fraction was observed from upper to lower topographic positions. The enset field had significantly higher soil pH, OC, TN, and K+ contents than crop field. A significantly higher available P of 16.61 mg kg−1 was measured from lower slope position followed by 14.08 mg kg−1 in middle slope. The upper slope position had the highest exchangeable acidity of 3.09 cmol(+) kg−1), followed by middle slope with 2.77 cmol(+) kg−1), 2.45 cmol(+) kg−1) in the lower slope position. Grain yield and above ground biomass decreased from lower slope to middle slope and upper slope positions. These observed variations in soil properties and crop yield among land uses and topographic positions underscore the necessity for tailored soil management strategies and agronomic practices specific to land use types and the specific localized topographic conditions to optimize agricultural productivity.